PATRIARKI DAN RESISTENSI PEREMPUAN DALAM TRADISI SAWER PERNIKAHAN DI PULAU KANGEAN: IMPLIKASI TERHADAP PENDIDIKAN GENDER DI MASYARAKAT MADURA - Aqiq Zaman Al Qayyis; Moh. Fauzi; Ahmad Yasid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The tradition of wedding offerings on Kangean Island, Sumenep, Madura reflects the complex dynamics of gender relations. This study aims to reveal the representation of patriarchy and forms of female resistance in this tradition, as well as its implications for gender education in society. The approach used is feminist ethnography, with data collection methods including participatory observation and in-depth interviews. The research findings indicate that the sawer tradition represents male dominance through economic and symbolic control, yet simultaneously serves as a space for women to employ various resistance strategies, such as forming social networks and managing financial independence. Although controversial for its portrayal of women as objects of entertainment, this tradition also opens opportunities for critical reflection in gender education. This study makes an important contribution to understanding local cultural practices that can be utilized as teaching materials in developing gender awareness in Madurese society.